Tax avoidance and accounting conservatism - Tobias Bornemann (Arbeitskreis Quantitative Steuerlehre (arqus), 2018)
This study analyzes the relation between accounting conservatism, future tax rate cuts and countries' level of book-tax conformity. Firms have an incentive to increase conservatism in financial reporting when a tax rate cut is imminent to shift taxable income into the lower taxed future. Using a panel of firms across 18 countries from 1995 to 2010 I find that conditional conservatism is positively and significantly associated with future tax rate cuts when book-tax conformity is high. This effect is particularly pronounced for firms that concentrate the majority of their operations in the country in which the tax rate is cut. In contrast, there is no significant relation between future tax rate cuts and unconditional conservatism.
Keywords: H21; H25; 330; accounting conservatism; tax rate cuts; book-tax conformity